The Process Of Building A Virtual Teacher According To Self-Regulated Learning In Teaching Maths In Primary Schools (International Journal of Scientific Research and Management (IJSRM), 2024)
Chatbot is a program that interacts with users via textual or auditory. Nowadays, Chatbots are widely used in jobs such as virtual assistants for customer care, product introduction, sales, etc. Chatbots have also been applied in many different aspects of the field of education thanks to the benefits it brings including high personalization, high interactivity, speed, accuracy, etc. A popular application of Chatbots in education is using Chatbots to teach. This article analyzes the benefits that Chatbots bring to the field of education, thereby providing a process for designing a teaching Chatbot for a specific lesson in the direction of self-regulated learning to help teachers and educators have orientation in using Chatbot in teaching.